Supporting a Responsive Transition to High School through a Summer Transition Camp - Cheryl R. Ellerbrock; Erin Parke; Jennifer Denmon (MDPI AG, 2023)
In this qualitative case study (n = 32), researchers sought to understand the ways a multi-day summer transition camp may help incoming ninth-grade students experience a developmentally responsive transition into high school. The findings revealed camp helped support students' procedural, social, and academic-related needs and concerns. Learning the school layout and policies helped support students' procedural-related needs and concerns. Promoting student-student, educator-student, and school-student relationships helped support students' social-related needs and concerns. Attending academic classes and communicating expectations for academic success helped support students' academic-related needs and concerns. A summer camp may foster a responsive transition and mitigate school failure, but must be developed and delivered based on students' developmental and transition-related needs and concerns. Furthermore, students must perceive camp activities as actually supporting their needs and concerns.